The relationship between sport and violence: how sports practice can be used as a tool to prevent violence, and how physical education teachers can help create a safe and peaceful school environment - Sousa, Rodger Roberto Alves de (Revista Interseção, 2025)
ABSTRACT This article presents a literature review and an empirical study on the relationship between sports and violence, focusing on violence prevention and the role of physical education teachers in creating a safe and peaceful school environment. The literature review highlights the positive and negative aspects of sports in relation to violence, as well as pedagogical strategies for violence prevention. The empirical study was conducted with physical education teachers from a public school, using questionnaires and interviews to investigate their perceptions of the relationship between sports and violence, and their practices for preventing violence in their work environments. The results indicated that teachers recognize the importance of sports in violence prevention, but also identify several factors that can contribute to violence in sports environments, such as aggressive behavior from coaches and parents and a lack of adequate supervision. Additionally, teachers reported using pedagogical strategies to promote inclusion, cooperation, and mutual respect, as well as to teach responsibility and fair play to their students. These results indicate that physical education teachers have a crucial role in preventing violence in sports and school environments, and highlight the importance of a collaborative approach between school, family, and community to address this social problem. Keywords: Sports. Violence. Physical Education teacher. Prevention. Pedagogical Strategies. A relação entre esporte e violência: como a prática esportiva pode ser usada como ferramenta para prevenir a violência e como os professores de educação física podem ajudar a criar um ambiente escolar seguro e tranquilo RESUMO Este artigo apresenta uma revisão de literatura e um estudo empírico sobre a relação entre esporte e violência, com foco na prevenção da violência e no papel do professor de educação física na criação de um ambiente escolar seguro e pacífico. A revisão de literatura destaca os aspectos positivos e negativos do esporte em relação à violência, bem como estratégias pedagógicas para prevenção da violência. O estudo empírico foi realizado com professores de educação física de uma escola pública, utilizando questionários e entrevistas para investigar suas percepções sobre a relação entre esporte e violência, e suas práticas para prevenir a violência em seus ambientes de trabalho. Os resultados indicaram que os professores reconhecem a importância do esporte na prevenção da violência, mas também identificam vários fatores que podem contribuir para a violência em ambientes esportivos, como o comportamento agressivo de treinadores e pais e a falta de supervisão adequada. Além disso, os professores relataram usar estratégias pedagógicas para promover a inclusão, a cooperação e o respeito mútuo, bem como para ensinar responsabilidade e fair play aos seus alunos. Esses resultados indicam que os professores de educação física têm um papel crucial na prevenção da violência em ambientes esportivos e escolares, e destacam a importância de uma abordagem colaborativa entre escola, família e comunidade para enfrentar esse problema social. Palavras-chave: Esporte. Violência. Professor de Educação Física. Prevenção. Estratégias Pedagógicas.